trans-Dichloridobis(dimethyl sulfoxide-κO)bis(4-fluorobenzyl-κC1)tin(IV): crystal structure and Hirshfeld surface analysis - Amin, N.A.M.; Hussen, R.S.D.; Lee, S.M.; Halcovitch, N.R.; Jotani, M.M.; Tiekink, E.R.T. (International Union of Crystallography, 2017)
The SnIV atom in the title diorganotin compound, [Sn(C7H6F)2Cl2(C2H6OS)2], is located on a centre of inversion, resulting in the C2Cl2O2 donor set having an all-trans disposition of like atoms. The coordination geometry approximates an octahedron. The crystal features C - H⋯F, C - H⋯Cl and C - H⋯π interactions, giving rise to a three-dimensional network. The respective influences of the Cl⋯H/H⋯Cl and F⋯H/H⋯F contacts to the molecular packing are clearly evident from the analysis of the Hirshfeld surface.